A computational study on molecular structure, multiple interactions, chemical reactivity and molecular docking studies on 6[D (−) α-amino-phenyl-acetamido] penicillanic acid (ampicillin). Issue 11 (23rd July 2016) - Shukla, Anuradha; Khan, Eram; Srivastava, Anubha; Tandon, Poonam; Sinha, Kirti
Abstract: Ampicillin 6[D (−) α-amino-phenyl-acetamido] penicillanic acid (AMP) is a β-lactam antibiotic that is active against both gram-positive and gram-negative. Due to industrial and biological importance of β-lactam antibiotics, an extensive quantum chemical study on AMP was carried out. The theoretical ground-state geometry and electronic structure of AMP are optimised by the DFT/B3LYP/6-311++G(d, p) method and compared with those of the crystal data. Four conformers have been found by potential energy surface scan. Among them, the geometry of the conformer-IV matches well with the experimental value, so we proceed with it. Natural bond orbital analysis has been used to analyse the stability of the molecule arising from hyperconjugative interactions and charge delocalisation. HOMO and LUMO have been plotted and analysed in order to describe the chemical reactivity of the molecule. MEP for these conformers shows that the negative potential is visualised over the O41 atom of C=O group of the molecule. Molecular docking studies show that the title molecule exhibits an antibacterial activity. The interpretation of diverse aspects of chemical bonding has been done by computing global and local reactivity descriptors. The variation of thermodynamic properties (such as C ° p, m, S ° m, H ° m ) with temperature has been studied theoretically. The present work will be helpful to systematically understand the structures and the electronic properties of AMP for studying the structure–activity relationship and to develop new drugs and their analytical methods.